2021
DOI: 10.1071/ch20093
|View full text |Cite
|
Sign up to set email alerts
|

The Trip to the Density Functional Theory Zoo Continues: Making a Case for Time-Dependent Double Hybrids for Excited-State Problems

Abstract: This account is written for general users of time-dependent density functional theory (TD-DFT) methods as well as chemists who are unfamiliar with the field. It includes a brief overview of conventional TD-DFT approaches and recommendations for applications to organic molecules based on our own experience. The main emphasis of this work, however, lies in providing the first in-depth review of time-dependent double-hybrid density functionals. They were first established in 2007 with very promising follow-up stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
109
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(121 citation statements)
references
References 148 publications
(243 reference statements)
8
109
0
Order By: Relevance
“…It accounts for double excitations perturbatively based on a CIS(D) 155,156 calculation, and it was shown to be one of the most reliable TD-DFA methods currently available. 122 Generally, it reproduces trends in both singlet-triplet gaps and oscillator strengths faithfully. Occasional outliers of singlet-triplet gaps lead to missing molecules that would be inverted, but not to misidentifying ordinary structures as INVEST molecules (Figure 3a).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…It accounts for double excitations perturbatively based on a CIS(D) 155,156 calculation, and it was shown to be one of the most reliable TD-DFA methods currently available. 122 Generally, it reproduces trends in both singlet-triplet gaps and oscillator strengths faithfully. Occasional outliers of singlet-triplet gaps lead to missing molecules that would be inverted, but not to misidentifying ordinary structures as INVEST molecules (Figure 3a).…”
Section: Discussionmentioning
confidence: 75%
“…22,116 Therefore, refined models accounting for double excitations are required to describe the low-energy excited electronic states of INVEST emitters appropriately. TD-DFAs need to be double-hybrid or higher in their rung 41,122 or have to be used as spin-flip variant with a well-behaved triplet state as reference. 123 Accordingly, a four-state model has been proposed as minimal model to describe the low-energy excited states of INVEST molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 77 80 The connection between the fraction of the exact exchange in the RS XC energy and the optimal range-separation parameter for the nonempirical functionals was presented by Adamo et al 78 Later, it was demonstrated that these parameters are in line with the results obtained by relying on the so-called optimally tuned procedure. 79 The only excited-state RS-DH approach proposed 81 and carefully benchmarked 82 , 83 recently by Goerigk and co-workers also originated from this scheme.…”
Section: Introductionmentioning
confidence: 99%
“…Lars Goerigk and co-author Marcos Casanova-Paéz (University of Melbourne) start out with an account, 'The Trip to the Density Functional Theory Zoo Continues: Making a Case for Time-Dependent Double Hybrids for Excited-State Problems', [1] which is written for the general users of timedependent (TD) density functional theory (DFT). It is written in a way that also makes it useful for scientists who have little prior knowledge in the area.…”
mentioning
confidence: 99%